Domestic animal proteomics in the 21st century: a global retrospective and viewpoint analysis - Almeida, André M. (2021)
Animal production and health are of significant economic importance, particularly regarding the world food supply. Animal and veterinary sciences have evolved immensely in the past six decades, particularly in genetics, nutrition, housing, management and health. To address major challenges such as those posed by climate change or metabolic disorders, it is of utmost importance to use state-of-the-art research tools. Proteomics and the other post-genomic tools (transcriptomics or metabolomics) are among them. Proteomics has experienced a considerable development over the last decades. This brought developments to different scientific fields. The use and adoption of proteomics tools in animal and veterinary sciences has some limitations (database availability or access to proteomics platforms and funding). As a result, proteomics' use by animal science researchers varies across the globe. In this viewpoint article, we focus on the developments of domestic animal proteomics over the last decade in different regions of the globe and how the researchers have coped with such challenges. In the second part of the article, we provide examples of funding, educational and laboratory establishment initiatives designed to foster the development of (animal-based) proteomics. International scientific collaboration is a definitive and key feature in the development and advancement of domestic animal proteomics. SIGNIFICANCE: Animal production and health are very important for food supply worldwide particularly as a source of proteinaceous foods. Animal and veterinary sciences have evolved immensely in the last decades. In order to address the major contemporary challenges facing animal and veterinary sciences, it is of utmost importance to use state-of-the-art research tools such as Proteomics and other Omics. Herein, we focus on the major developments in domestic animal proteomics worldwide during the last decade and how different regions of the world have used the technology in this specific research field. We address also major international efforts aiming to increase the research output in this area and highlight the importance of international cooperation to address specific problems inherent to domestic animal proteomics.